A Destiny Shaped by Water : A Diagnostic of Water Supply, Sanitation, and Hygiene and Poverty in Niger - World Bank (World Bank, Washington, DC, 2019)
The Water Supply, Sanitation, and Hygiene (WASH) Poverty Diagnostic (PD) in Niger is part of a global initiative to improve evidence on the linkages between WASH and poverty. The Diagnostic provides a detailed analysis of sector status, strengths, and weaknesses to inform the attainment of the new Sustainable Development Goals (SDGs) that aim for universal access to safely managed water supply and sanitation.